Historical Analysis Of The Development Of Number Theory In The Islamic Intellectual Tradition - Hardika Saputra; Yayuk Primawati; Ramadhani Dewi Purwanti (Asosiasi Riset Ilmu Pendidkan Agama dan Filsafat Indonesia, 2024)
This article explores the contributions of Muslim scholars to the development of number theory and their impact on global mathematics. Through a qualitative research method with a library research approach, the study examines the works of notable figures such as Al-Khwarizmi, Al-Kindi, Omar Khayyam, and Al-Karaji, highlighting their roles in refining and advancing mathematical concepts. It also discusses the philosophical and theological influences that shaped their approaches to numbers and mathematics. The article further analyzes the transmission of these ideas to the Western world and their subsequent influence on Western mathematical traditions. The findings suggest that Muslim scholars played a pivotal role in the evolution of number theory by integrating knowledge from various civilizations and introducing innovative mathematical frameworks. Despite certain limitations regarding source accessibility and reliance on historical interpretations, the research underscores the enduring impact of these contributions on the development of modern mathematics.